Articulated Structures of D-A Type Dipolar Dye with AIEgen: Synthesis, Photophysical Properties, and Applications - Kim, Na Hee (Materials (Basel), 2020)
Articulated structures of naphthalene-based donor (D)-acceptor (A) type dipolar dye and aggregation-induced emission luminogen (AIEgen) based on tetraphenylethylene (TPE) were synthesized, and their photophysical properties were analyzed for the first time. There are many fluorophore backbones, which have dipolar structure and AIEgen. However, there has been neither property analysis nor research that closely articulates DA and AIE through non-conjugation linker. We have therefore prepared two representative fluorophores; DA-AIE series (DA-AIE-M and DA-AIE-D), and characterized their UV/vis absorption and emission properties with quantum chemical calculations. In addition, we utilized the unique photophysical properties of DA-AIE-D for monitoring a trace of dimethyl sulfoxide (DMSO) in aqueous media, including real water samples.